تأصيل مصطلح السياحة في القرآن والسنة - محمد ضياء الحفيظ بن فتح ياسين; محمد رصفان سازرين بن محمد صوفي (Journal of Islam in Asia (E-ISSN 2289-8077), 2023)
استهل هذا البحث بتناول تأصيل مصطلح السياحة في القرآن والسنة؛ لأن مصطلح السياحة ورد في القرآن والسنة في سياق يحتمل معنىً إيجابيًّا وسلبيًّا، وكذا ورد في صيغة الأمر والنهي. وهذا يتطلب إعداد دراسة لتأصيل مصطلح السياحة؛ لأن تحديد المصطلح لها دور في توضيح الأمور ذات الصلة بالسياحة لغة وشرعًا. ويستخدم البحث المنهج الاستقرائي الوصفي والتحليلي المقارن؛ حيث يجمع البحث الآيات وبعض الأحاديث التي تحتوي على كلمة السياحة ومرادفتها. ومن أهم نتائج البحث: أن كلمة السياحة ومشتقاتها في القرآن والحديث تستخدم لمعان عدة، وهي: السير خارج البلد المسكون بقطع المسافة البعيدة، والسير بالتجول داخل البلد، ولكن بقطع مساحة كبيرة لا مسافة بعيدة، ويستعمل صفة لجريان الماء وظهوره، والاتساع، والصيام، والجهاد، وطلب العلم، ولزوم المساجد، والرهبنة وكذا اسم العلم. وتوصل البحث –أيضًا- إلى أن معنى السياحة في القرآن والسنة هي عبارة عن حبس النفس إما بالصيام أو بتحمل مشقة التجول على وجه الأرض. وكما توصل البحث بناء على المفهوم المعاصر للسياحة، أن السياحة أمر إيجابي وأنها تُعدّ من العبادة المأمورة بها Abstract: The focus of the research is to identify to root meaning of siyahah (trans. Tourism) in the Qur’an and Sunnah. This is due to the fact that siyahah was mentioned in the Qur’an and Sunnah in both of positive and negative meanings, as well as in the form of command and prohibition. Thus, the understanding of the root of the term in both revelations sources is crucial. It also contribute in clarifying matters related to tourism, both in terms of common understanding and in Islamic law. The research uses the inductive, descriptive and comparative analytical methods, where the research collects verses and some hadiths that contain the word siyahah and its synonym. One of the most important results of the research: that the word siyahah and its derivatives was used in the Qur’an and hadith for several meanings, namely: travelling outside the inhabited state by crossing a long distance; errands within the state, but by crossing a large area not a long distance; the flowing on surface of a water; breadth; fasting; jihad; seeking knowledge; keeping oneself in mosque; monasticism, as well as the names of objects. The research also concluded that the root meaning of siyahah in the Qur’an and Sunnah is enduring oneself either by fasting or facing the difficulties of roaming on the earth. The research has also determined that the contemporary concept of siyahah fall in a positive side of those meanings, and it is a thing commanded by the revelation. Keywords: Islamic tourism, Tourism in Qur’an, Tourism in Sunnah, Tourism as ibadah.